Motivational Aspects for Voluntary Participation in Open Government Platforms: A Look from the Users Perspective - Lima, Joel Alves; Correia, Jorge Silva; Souza, Marcílio Ferreira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2020: Anais do XVI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2020.13779, 2020)
Governments have taken important initiatives to strengthen social control and increase the effectiveness of their actions, especially those aimed at Open Government, which seek to publicize data to encourage social participation in public management through technology platforms. Thus, the objective of this research was to identify the set of motivational aspects that encourage citizens to use the Open Government electronic platforms. In the method, 67 semi structured interviews were conducted with individuals with experience in these platforms and the data were analyzed qualitatively with the support of Atlas.ti software. The results obtained revealed 18 users´ motivational aspects for participation in Open Government platforms, which could be combined in technological, altruistic and affective factors. The affective factors (indignation, duty of citizens, contributing something, social improvement, seeking solutions, transparency and accountability) are what motivate users the most.